Формування навичок читання англомовної наукової літератури студентів-магістрів немовних спеціальностей - Гедз, Світлана Федорівна; Hedz, Svitlana F. (Східноєвропейський національний університет імені Лесі Українки, 2018)
Статтю присвячено вивченню способів формування навичок читання англомовної в студентів-магістрів немовних спеціальностей. Запропоноване визначення поняття «наукової комунікації», яка трактується як психо-лінгво-ментальна діяльність учасників спілкування за допомогою мовного коду, що направлена на одержання і передачу певної інформації наукового змісту. Подаються зразки вправ, які виконуються на різних етапах роботи над науковим текстом. Підкреслюється необхідність навчання студентів роботі над словником та їх ознайомленню із словами, які є «фальшивими друзями» перекладача. This article is dedicated to the investigation of means of developing reading skills of the English scientific literature in students getting master`s degree in non-linguistic specialities. The definition of the notion “scientific communication” is suggested. It is understood as a psycholinguistic and mental activity of the participants in communication with the help of linguistic code aimed at receiving and transferring scientific information. The examples of the exercises on learning phrasal verbs, idioms and metaphors characteristic of scientific prose which are done on different stages of the work on scientific texts are proposed. The necessity of teaching students how to work with dictionaries and the need of learning the words which are “translator`s false friends” are emphasized. Learning to work with the vocabulary involves not only the formation of the ability to choose the meaning of the word with the focus on the context in which it is used, but also the development of the necessary skills related to the study of word-formation elements such as suffixes, prefixes and the stems of words, which were borrowed from other languages into English. Exercises on the word formation are done before and after the study of a certain scientific text. The purpose of doing pre-text exercises is to remove possible language difficulties connected with the understanding of the text. Post-text tasks are aimed at consolidating reading skills and at their use in the work on the other scientific texts. Pre-text exercises should not disclose the content of the scientific text in order not to weaken the students' interest in reading it. Before reading the text it is important to familiarize students with the abbreviations used in the text. It is also advisable to demonstrate to students the difference between the meaning of certain lexical units used in everyday and in scientific speech. In the process of working on the scientific text, it is necessary to teach students to recognize the causal relationships between its individual fragments as well as to distinguish the author`s hypothetical statements from those which describe facts requiring no proof.
Developing Reading Skills of the English Scientific Literature in Students Getting Master`s Degree in Non-Linguistic Specialities
Keywords: наукова комунікація; читання; наукова література; науковий текст; науковий стиль; scientific communication; reading; scientific literature; scientific text; scientific style